Learning Activities of Students using Developed Innovative Pop-up Book - Adelila, Sri; Prawoto, Agung (Universitas Medan Area, 2018)
This study was aimed to describe learning activities of students using innovative developed pop-up book on colloids. The development method used was research and development (R & D) through ADDIE model. Subjects in this study were thirty one of senior high school students from grade XI, SMAN 4 Banda Aceh which were taken by purposive sampling. Data of studentsâ activities were collected using observation sheet. Besides that, the eligibility of developed pop-up book was measured using questionnaire which was filled by expert validators. Results showed that the eligibility of pop-up book was found to be 73.50 percent belong to the category of decent. In addition, the learning activities were found to be increased from 76.21 to 86.25 percent from first meeting to second meeting, respectively. It concluded that the learning activities of students using developed innovative pop-up book on colloids material were very good.